The roles of Muslim women in civil society in promoting values principles for building peace : action guide from the Qur'an - Bahari, Che Amnah; Abdullah, Fatimah (2018)
The whole world, the Muslim in particular has witnessed conflicts in different areas, which have hindered the developmental efforts of the nations concerned. It should be learned that most victims of these conflicts are women and children. This article attempts to elaborate the role of Muslims Women as a crucial segment in civil society in initiating peace building through nurturing process. It maintains that the adoption of the principles and values derived from the Qur’ān and Sunnah of the Prophet is necessary as a process of lifelong learning. Those identified values constituted the framework of this article and it adopts the textual analysis method. This article concludes that through the implementation of those values and frameworks for peace building, women as one of the important segments of civil society are able to play significant role towards initiating peace building and promoting peaceful co-existence in pluralistic society. Keywords: Muslim women, civil society, peace building and peace co-existence